Pressure-induced left ventricular hypertrophy in canine model of aortic stenosis using nylon tie (Acta Scientiarum. Biological Sciences, 2020)
The aim of this study was to develop an experimentally-induced canine model of left ventricular hypertrophy through banding of the ascending aorta using nylon ties. Seven clinically normal dogs free of cardiovascular disease were used. Nylon tie was used in banding the mid-ascending aorta. Clinical, radiographic and echocardiographic evaluations were done at 1.5, 3 and 6 months. Dogs were euthanized at 6 months for post mortem and histopathological evaluation. Clinically, dogs did not exhibit any signs of cardiovascular disease at 1.5 or 3 months, while at 6 months two dogs (28.6 %) exhibited mild weight loss, exercise intolerance and heart murmurs. Radiographic evaluation revealed significant increase in cardiac size only at 6 months based on measurement of the cardiothoracic area evaluation. Echocardiography revealed increased left ventricular wall thickness starting from 1.5 month, although this increase was statistically significant at 3 and 6 months (p > 0.05). Left ventricular hypertrophy was confirmed by post mortem examination. Histopathological sections of left ventricle in all dogs demonstrated myocyte hypertrophy and interstitial fibrosis. This model simulates the naturally occurring ventricular hypertrophy using a rapid and economic technique. Such models are required to understand pathogenesis of heart disease and to develop effective treatment strategy.